2017
DOI: 10.21767/1791-809x.1000476
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden in Pediatric Asthma: A Systematic Review

Abstract: Background: As delivering care is an inherent part of becoming parents, providing high level care to the child with health problems might be a burden for the caregivers by affecting their physical and mental health. The best way to understand the negative effects of caring process of the children with a chronic disease like asthma is to inquire caregiver burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…This aligns well with the findings of other researchers who reported that psychosocial determinants are more crucial in predicting parental QOL than medical and demographic variables (Hatzmann et al 2009, Fidika, Salewski, & Goldbeck 2013. In a systematic review on QOL of parents caring for children with Asthma involving 22 studies, Ekim and Ocakci (2016) found that providing higher level of care to child can be burdensome and have negative effect on the physical and psychosocial health of caregivers. The review supports the findings of this study that the QOL of caregivers is lower.…”
Section: Data Collectionsupporting
confidence: 89%
“…This aligns well with the findings of other researchers who reported that psychosocial determinants are more crucial in predicting parental QOL than medical and demographic variables (Hatzmann et al 2009, Fidika, Salewski, & Goldbeck 2013. In a systematic review on QOL of parents caring for children with Asthma involving 22 studies, Ekim and Ocakci (2016) found that providing higher level of care to child can be burdensome and have negative effect on the physical and psychosocial health of caregivers. The review supports the findings of this study that the QOL of caregivers is lower.…”
Section: Data Collectionsupporting
confidence: 89%
“…This was not expected as literature has noted the increased burden of care for a chronically-ill individual [ 9 , 10 , 12 16 ]. This has been shown in children diagnosed with asthma [ 12 , 16 ], genetic conditions [ 13 ], Autism Spectrum Disorders [ 15 ], Spina Bifida [ 19 ] and mental health concerns [ 14 ]. It was thus surprising that care for CI children in this sample did not result in either a decreased VAS or index score in the caregiver.…”
Section: Discussionmentioning
confidence: 87%
“…Instruments such as the CarerQoL have yielded important information in the spill-over effect of caring for an ill adult, but little work has been done in measuring the spill-over effect in caring for ill children. It has however been noted that providing care to a child with a chronic condition is burdensome and may affect the physical and psychosocial health of the caregiver negatively [ 12 ]. This is attributed to the fact that delivering this care is mostly unexpected, complex and often leads to extra expenses for medication and equipment as well as extended time for caring of the child [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A child's chronic illness, such as asthma, induces excessive stress and physical and psychological burdens to parents and the whole family (Ekim and Ocakci 2016;Kim and Yoo 2007;Silva et al 2015). At the same time, caregiver stress is known to contribute to the development and course of child asthma, with depression in the parent predicting poorer asthma control (Celano 2006;Rioseco et al 2017;Rodriguez et al 2017;Wood et al 2015).…”
Section: Parental Burdenmentioning
confidence: 99%